(untitled) (Fiep Bulletin - online, 2011)
The purpose of this study was to correlate anthropometric variables and physical youth indoor soccer players, category sub 13. The sample consisted of 18 male athletes, aged 11.8 ± 1.2 years. Were Performed tests of flexibility, lower limb power, agility, speed and aerobic power. For the evaluation of weight and height were used a mechanical scale with stadiometer wellmy R110, the analysis of fat percentage was performed with the scientific Cescorf skinfold equation and Slaughter, 1988; the total weight was fragmented by weight bone, muscle, and residual fat (De Rose, 1984). Statistical analysis was performed with SPSS 10, using descriptive statistics and correlation of Person with significance level p <0.05. There were no significant correlations between anthropometric variables and variables of flexibility, agility and speed. The fat percentual presented moderate correlation (r =- 0.514) with VO2 max. The weight (r = 0.541), muscle mass (r = 0.725), residual mass (r = 0.539) and lean mass (r = 0.647) showed significant correlations with the long jump, but only muscle mass (r = 0.575) showed moderate correlation with the vertical. Despite that there are no strong correlations between anthropometric variables and physical performance is analyzed, the athletes with lower values of% fat tend to have better aerobic power, while individuals with greater lean body mass seem to have better results in the horizontal jump test. Athletes with higher muscle mass tend to have better results in both tests of power of lower limbs.